Reconceptualizing Podcasts as Multi-Functional Learning Media to Enhance Academic Discussions among PGMI Students - Nurul Ramadhani (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2025)
This study aims to determine the effectiveness of the use of podcasts as a source of information, interaction and education in improving the learning discussions of PGMI students in Semester V at the University of Muhammadiyah Mataram. The background of this research is the lack of students using podcasts as a source of information, interaction and education as a serious academic tool for discussions that still rely on books, and cellphones. This study uses a qualitative method of phenomenological approach, namely to understand students' subjective experiences related to the use of podcasts. The informants of this research were 4 students, then the sample determination technique was using Purposive Sampling , each cycle consisted of core stages, namely observation, interview procedures, and documentation procedures. The results of the study show that the use of podcasts as a source of information, interaction and education can actually increase the learning discussions of PGMI students. This can be an effective learning method for students. Through the podcast program, PGMI students can share information about light discussions about education. Moreover, podcasts can increase the learning flexibility of PGMI students of the University of Muhammadiyah Mataram.